Sabah traditional music: How Covid19 expose the industry fault lines and what can be done - Roslee Wahid; Andrew Poninting (Akademi Seni dan Teknologi Kreatif, UMS, 2021)
The purpose of this is to examine the effects of the unwanted pandemic towards music studies specifically the Sabah traditional music scene. Observation data collection method combined with interview with informant used as participatory study, because the researcher has to immerse himself in the actual music industry situation. Results shows that while measures been taken to ensure continuity and progress, the lack of actual asses to the music instruments, performances and traditional music events are regrettable and in desperate needs of improvement. This study would be able to ameliorate the implementation of the matter to suits the current situation of music education and performance particularly the Sabah traditional music scene.